Review on the state of GIS application in secondary schools in the southern African region. Issue 2 (4th May 2019) - Mzuza, Maureen K.; Van Der Westhuizen, Christo P.
ABSTRACT: The use of geographical information systems (GIS) is attracting growing global enthusiasm among scholars and in the scientific world. Due to the significance of GIS and the increased demand for its use, its application in secondary school education has also become very important at both national and international levels. This paper reviews the current state of GIS application in southern African secondary schools. Although GIS is included in the education curriculum in several African countries, some countries still trail behind. Furthermore, despite the fact that good progress has been made with GIS education, many learning institutions in Africa still face challenges regarding its development and application as a teaching and learning tool. The main problems identified in this review include the absence of GIS education in secondary school curricula; the shortage of experienced teachers; the lack of knowledge and technical expertise; the unwillingness of teachers to change their mode of teaching; a shortage of funds, and inadequate resources. This review is hoped to inform bodies of scholars about the state of GIS application in secondary school education in southern Africa and to infuse interest and collaboration across borders to exchange knowledge and support.